Cross-cultural adaptation and validation of the family needs assessment scale for Brazilian families of children and adolescents with disabilities - Nunes, Ana Célia; Santos, Daniela Bitencourt; Leite, Márcio Fernandes Alves; Gràcia, Marta; de Souza Della Barba, Patricia Carla (Frontiers in Education, 2023)
Introduction In Brazil, there are few studies that investigate the support needs of families that have handicap children in their daily context. This study aims to adapt and validate the Family Needs Assessment (FNA) scale for use with families of children and adolescents with disabilities in Brazil. Method Two studies were conducted. The first study involved the cross-cultural adaptation of the scale, resulting in the Brazilian version of the FNA, which is called Avaliação das Necessidades da Família (ANF). The FNA comprises 49 items with high internal consistency (α = 0.98). The second study validated the FNA using a sample of 151 families with children and adolescents with disabilities. Results The structure of the scale was confirmed using Structural Equation Modeling (SEM), which grouped 46 items into seven dimensions. The scale demonstrated good fit (RMSEA = 0.041, SRMR = 0.063), satisfactory convergent validity (rs = −0.27, p < 0.001), and high levels of reliability (α = 0.92, ω = 0.94) and test–retest consistency (R1F = 0.98). Discussion The FNA is a valid, reliable, and accurate measure for assessing the needs of Brazilian families with children and adolescents with disabilities under 18 years of age.